النسبية في الجزاء الجزائي - أميرة شرابشة; نادية بن سعدي (My University, 2022)
Summary The criminal penalty structure appears clear through the law and the judiciary together. Each complements the other in the penal system. The legal intention of a penal sanction is evidenced by the fact that it exists through a campaign of legal excesses, which is limited by the legislation to a series of legal texts that serve as an impenetrable barrier. As for the judicial circumstances, they are those that the legislature has granted to the criminal judge, which have left the judge with discretion and skill through a combination of circumstances and circumstances surrounding the crime, as well as with regard to the perpetrator himself. This is in addition to the aggravating circumstances, whether public or private, in which the legislature aims to deter the perpetrator and protect society from crime. As for the proportionality of a penal sanction in terms of the judiciary, the authority of a criminal judge includes the possibility of dropping the prescribed penalty limit using, as we mentioned, the relativity of the legal penalty through the effect of mitigating circumstances on the various types of penalties, whether they are original in nature (such as the death penalty and the penalty that deprives of liberty) or complementary penalties, all of which fall into one category, which is an attempt to mitigate the impact of the penalty through these circumstances. ………………… ملخص المذكرة: تظهر نسبية الجزاء الجزائي واضحة من خلال القانون و القضاء معا فكل واحد منهما يكمل الآخر في المنظومة العقابية، فأما نسبية الجزاء الجزائي من حيث القانون فنستدل على وجوده من خلال جملة الأعذار القانونية التي حصرها المشرع في مجموعة من النصوص القانونية التي تعد بمثابة حاجز لا يمكن اختراقه، و أما الظروف القضائية فهي تلك المكنة التي منحها المشرع للقاضي الجزائي و التي تركت لفطنة و نباهة القاضي من خلال حوصلة من الملابسات و الظروف المحيطة بالجريمة و كذا ما تعلق بالجاني في حد ذاته، ضف إلى ذلك ظروف التشديد سواء كانت ظروفا عامة أو خاصة يهدف من ورائها المشرع إلى ردع الجاني و حماية المجتمع من الجريمة، و أما عن نسبية الجزاء الجزائي من حيث القضاء فتضمن سلطة القاضي الجزائي في إمكانية النزول عن الحد المقرر للعقوبة مستعينا كما ذكرنا سابقا بنسبية الجزاء القانوني من خلال تأثير تلك الظروف المخففة على مختلف أنواع العقوبات سواء كانت أصلية بطبيعتها كالإعدام و العقوبة السالبة للحرية و الغرامة أو العقوبات التكميلية و كلها تصب في مصب واحد و هو محاولة التخفيف على الجاني أثر العقوبة من خلال هذه الظروف. ……………….. Résumé La structure des sanctions pénales semble claire dans la loi et dans le système judiciaire. Chacune est complémentaire de l’autre dans le système pénal. L’intention légale d’une sanction pénale est démontrée par le fait qu’elle existe à travers une campagne d’excès juridiques, qui est limitée par la législation à une série de textes juridiques qui servent de barrière impénétrable. En ce qui concerne les circonstances judiciaires, ce sont celles que le législateur a accordées au juge pénal, qui ont laissé au juge le pouvoir discrétionnaire et la compétence en raison d’une combinaison de circonstances et de circonstances entourant le crime, ainsi qu’en ce qui concerne l’auteur lui-même. Cela s’ajoute aux circonstances aggravantes, publiques ou privées, dans lesquelles le législateur vise à dissuader l’auteur du crime et à protéger la société contre le crime. En ce qui concerne la proportionnalité d’une sanction pénale par rapport à la magistrature, l’autorité d’un juge pénal inclut la possibilité d’abandonner la limite de peine prescrite en utilisant, comme nous l’avons mentionné, la relativité de la peine légale par l’effet de circonstances atténuantes sur les différents types de peines, qu’elles soient de nature originale (comme la peine de mort et la peine qui prive de liberté) ou complémentaires, Tous ces éléments entrent dans la même catégorie, c’est-à-dire qu’il s’agit d’une tentative d’atténuer l’incidence de la pénalité dans ces circonstances.